1999
DOI: 10.1002/(sici)1096-9926(199904)59:4<227::aid-tera7>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adult cancer after intrauterine exposure to ionizing radiation

Abstract: Since the reports in 1956 and 1958 that in utero radiation was associated with an increased risk of leukemia and solid cancers during childhood, this issue has been debated. Many epidemiological studies have been performed. Evidence for a causal association derives almost entirely from case‐control studies, whereas practically all cohort studies find no association, most notably the series of atomic bomb survivors exposed in utero. Although it is likely that in utero radiation presents a leukemogenic risk to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 45 publications
1
70
0
4
Order By: Relevance
“…A causal explanation of this association is not universally accepted (Boice and Miller, 1999), but Doll and The cancer epidemiology of radiation R Wakeford Wakeford (1997) concluded that the evidence strongly suggests an underlying cause-and-effect relationship. Recently, Wakeford and Little (2003) showed that the ERR coefficient that may be derived from the largest case-control study of childhood cancer and obstetric radiographic examinations (the OSCC) is consistent with the estimate obtained from the Japanese atomic bomb survivors irradiated in utero who received, on average, doses an order of magnitude higher, although the uncertainties associated with this comparison imply that any inference of linearity can only be tentative.…”
Section: Introductionmentioning
confidence: 99%
“…A causal explanation of this association is not universally accepted (Boice and Miller, 1999), but Doll and The cancer epidemiology of radiation R Wakeford Wakeford (1997) concluded that the evidence strongly suggests an underlying cause-and-effect relationship. Recently, Wakeford and Little (2003) showed that the ERR coefficient that may be derived from the largest case-control study of childhood cancer and obstetric radiographic examinations (the OSCC) is consistent with the estimate obtained from the Japanese atomic bomb survivors irradiated in utero who received, on average, doses an order of magnitude higher, although the uncertainties associated with this comparison imply that any inference of linearity can only be tentative.…”
Section: Introductionmentioning
confidence: 99%
“…Even if one accepts the controversial concept that the embryo is more sensitive to the carcinogenic effects of radiation than the child is, the risk at these low exposures is much smaller that the spontaneous risks (Table 1). Furthermore, other studies (16)(17)(18) indicate that the estimate of the risk of radiation-induced leukemogenesis made by Stewart et al (15) is exaggerated. Table 1 presents the spontaneous risks facing an embryo at conception and the additional risks that would come from a low exposure of ionizing radiation (0.05 Gy).…”
Section: Risks To the Embryo From Ionizing Radiationmentioning
confidence: 97%
“…However, when the exposure exceeds the threshold dose, the risks of radiation exposure to the human embryo include embryonic loss, growth retardation, congenital malformations, microcephaly and mental retardation, infertility, and carcinogenesis (with the magnitude of the oncogenic risk to the fetus being controversial) (15)(16)(17)(18).…”
Section: Risks To the Embryo From Ionizing Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…These well established risk factors, i.e., family history, reproductive and menstrual history, and history of benign breast disease, are estimated to account for only about 40 % of breast cancer cases [17]. Childhood exposure to ionizing radiation [18][19][20], adult alcohol consumption [21], and obesity [7,22,23] also increase the risk of developing breast cancer. However, these risk factors are unlikely to account for the remaining cases of the disease [2,7,24] suggesting that there are still unidentified causes of breast cancer.…”
mentioning
confidence: 99%